Features of formation of information signals of resonant measuring converters with aperture and probe sensing elements - Bondarenko, I.N.; Васильев, Ю.С. (Radiotekhnika, 2018)
The effect of changing the interaction conditions of the aperture or probe sensitive elements of resonant measurement converters (RMC) with the objects of investigation on the process of formation of basic information signals is analyzed. The obtained experimental results allow us to state that the analytical relationships used to describe the influence of the parameters of the investigated objects on the quality factor and the resonance frequency of the RMC and a priori assume the invariability of its connection with the measuring system are not observed in practice.